National Health Care data system analysis of glaucoma surgery activity in France in 2016. Issue 2 (17th June 2021) - Dufournet, Julie; Chiquet, Christophe; Bouisse, Magali; Francois, Patrice; Bron, Alain; Boussat, Bastien; Daien, Vincent; Bourcier, Tristan; Robert, Pierre‐Yves; Aptel, Florent
Abstract: Purpose: To describe the glaucoma surgery offer in France in 2016. Methods: We used the French National Health Care System database to identify all medical procedures carried out in 2016. The study investigated the entire population aged 30 years and older that had undergone glaucoma surgery, alone or combined with another surgery. We calculated the incidence of surgeries per 100 000 inhabitants 30 years of age and older performed by ophthalmologists carrying out at least 50 procedures annually, the number of surgeons doing these surgeries, the mean age of these practitioners, and the number of surgeons older than 55 years. Results: In 2016, 16 854 glaucoma surgeries were performed in patients aged 30 years and older, for an incidence of 40.8 per 100 000 inhabitants aged 30 years and older. The most frequent procedure performed was trabeculectomy followed by non‐penetrating deep sclerectomy (16.7 and 11.7, respectively, per 100 000 inhabitants 30 years of age and older). Private practice glaucoma surgery accounted for 47% of the activity of surgeons performing at least 50 surgeries per year and 60% of the total surgical activity. Of the private practice ophthalmologists performing at least 50 glaucoma surgery procedures per year, 58.5% were over 55 years of age, and 23.5% of public hospital ophthalmologists were over 55 years of age. Conclusions: This study demonstrates that surgeons performing glaucoma surgeries are often older. It is necessary to take note of the country's educational capacity to ensure that the number of ophthalmological surgeons remains adapted to demand.